The Analysis of Luckin Coffee’s Financial Fraud Based on GONE Theory - Zhang, Keyi; Shi, Haonan (Simen Owen Academic Proceedings Series, 2025)
On April 1, 2020, Luckin Coffee, once celebrated as the "Pride of the Nation," faced intense public scrutiny following the exposure of a large-scale financial fraud scandal. The severity and widespread consequences of this incident significantly disrupted the stable development of the market economy. This paper reviews the Luckin Coffee financial fraud case, providing a comprehensive analysis of its accounting manipulation techniques, and applies the GONE theory to explore the underlying motivations behind the misconduct. By examining the case through the four dimensions of the GONE framework, the study identifies targeted preventive measures to mitigate the risk of financial fraud. The findings indicate that while financial fraud may create a temporary illusion of profitability, it inflicts substantial long-term damage on internal corporate management structures. This research aims to assist enterprises in recognizing the serious consequences of financial misconduct and emphasizes the critical role of robust internal governance for corporate sustainability. In doing so, it contributes to the improvement of internal control mechanisms, reinforces regulatory functions, and ultimately enhances the overall quality of enterprise development.